Associations of parents’ and adolescents’ active travel behavior across various destinations – a sex/gender analysis - Beck, Franziska; Marzi, Isabel; Renninger, Denise; Demetriou, Yolanda; Engels, Eliane; Niermann, Christina; Reimers, Anne Kerstin (BMC Public Health, 2023)
Background Active travel behavior such as walking and cycling is associated with several health benefits. Especially the family environment seems to be important for active travel in children and adolescents. Currently, little is known regarding travel behavior in leisure time and associations of travel behavior within parent-adolescent dyads. Methods The present analysis is based on the German ARRIVE study (Active tRavel behavioR in the famIly enVironmEnt), which incorporated a large scale, representative cross-sectional online survey including 517 parent–child dyads consisting of adolescents (N = 517; boys = 263, girls = 254) aged 11–15 years and one of their parents (N = 517; fathers = 259, mothers = 258). Based on that survey which took place in June 2021 (during the COVID-19 pandemic), we calculated the prevalence of active travel to four commonly visited destinations (school/work, friends/relatives, shopping stores and recreational activities) using an adapted version of the travel to school questionnaire by Segura-Diaz JM, Rojas-Jimenez A, Barranco-Ruiz Y, Murillo-Pardo B, Saucedo-Araujo RG, Aranda-Balboa MJ, et al. (Int J Environ Res Public Health 17(14), 2020). In addition, we investigated the associations between parents’ and adolescents’ travel behavior using scores for school/work, leisure time (friends/relatives, shopping stores and recreational activities) and overall (school/work and leisure time). Results Across all destinations, prevalence of active travel in adolescents (63.08%) was higher than in parents (29.21%). Active travel to school (47.33%) as well as to work (20.43%) indicated the lowest prevalence. Linear regression models revealed significant associations in overall active travel between mothers and adolescents (girls: β = 0.308, p < 0.001; boys: β = 0.302, p = 0.001) and in leisure time active travel behavior between mothers and daughters (β = 0.316, p < 0.001). Related to school/work active travel there were no associations between parents and adolescents. Conclusion The associations between adolescents’ and parents’ travel behavior differ depending on gender: they are solely seen in mother-adolescents dyads. Furthermore, our findings conclude that travel is a routine and independent of the destinatio